Prevalencia y características clínicas del deterioro cognitivo en adultos mayores en pobladores de zonas urbanas en el distrito de Iquitos- 2025 - Silva Guerra, Hillary Mariela Mercedes (2025)
Objective: To describe the prevalence and clinical and epidemiological characteristics of cognitive impairment in older adults from urban areas of the district of Iquitos during 2025. Methods: Prospective observational study with an analytical, cross-sectional design. A total of 399 adults aged 65 years and older from the district of Iquitos were enrolled and administered a sociodemographic questionnaire, a clinical questionnaire, and the Mini-Mental State Examination (MMSE). Results: Cognitive impairment was identified in 40.6% of older adults (95% CI: 35.8 to 45.4). In univariate analysis, 263 were women and 136 men; the mean age was 74.6 ± 7.1 years. Regarding marital status, 39.1% were married, and with respect to occupation, 50.6% reported being employed; mean years of schooling were 8.4 ± 3.4. Fifty older adults had diabetes only, 186 had hypertension only, and 21 had both diabetes and hypertension. Depression or anxiety was reported by 172 participants; 236 engaged in regular physical activity; and 97.0% had access to health services. In bivariate analysis, the mean age in the group with cognitive impairment was 79.5 ± 7.1 years (p = 0.000). Years of schooling among those with impairment were 5.9 ± 3.2 (p = 0.000). Regarding marital status, in the impairment group 55 (48.7%) were married and 6 (5.3%) divorced (p = 0.010). Among those with impairment, 8.8% (10) had no comorbidities, 39.8% (45) had one, and 51.3% (58) had two or more (p = 0.002). Having two or more (≥ 2) comorbidities was significantly associated with the presence of cognitive impairment (p = 0.002). Finally, a healthy lifestyle was observed in 20.2% of those with impairment and 47.6% of those without impairment (p = 0.000). Conclusions: Variables such as age, years of schooling, marital status, number of comorbidities, healthy lifestyles, level of social support, and access to health services are associated with the development of cognitive impairment in older adults from urban areas of the district of Iquitos during 2025.